Two phase thermosyphon for high heat flux cooling application - Lee, Kai An. (2009)
Thermosyphons are a promising option for cooling high heat dissipating electronics because of their high effectiveness. At its simplest, a two-phase closed thermosyphon consists of an evaporator, a condenser and a heating base. Various parameters affect the heat transfer performance of thermosyphons. In this project, the effect of four parameters: fluid level, working fluid, graphite foam type and geometrical structure was investigated experimentally. The fluid fill levels investigated are 1.5 cm, 3.0 cm and 4.5 cm above the graphite foam surface. FC-72 and HFE-7000 were used as the working fluids. The graphite foams used in this study are POCO Graphite Foam and Koppers Foam (Kfoam). The geometrical structures of the foams are block and fin configuration. A series of experiments was carried out to study the influence of the above parameters on the steady-state heat transfer characteristics of a two-phase closed thermosyphon. The results showed that the fluid level has a significant effect on the heat transfer performance of the system but not on heater wall temperature. The working fluid has a significant effect on the heat transfer performance and wall temperature. FC-72 displayed better heat transfer performance on POCO foam but not on Kfoam. HFE-7000 resulted in a lower wall temperature than FC-72. In addition, the boiling phenomenon was found to be surface tension dominated. The type of graphite foam used has an effect on heat transfer performance. POCO Foam showed much better heat transfer performance than Kfoam only when FC-72 was used. The graphite foam geometry has a significant effect on heat transfer performance. Fin structure graphite foam performed better than block structure graphite foam.